R-peak time in clinically healthy dogs with different thoracic conformations. (February 2021) - Mateos Pañero, M.; Battaia, S.; Ramera, L.; Perego, M.; Santilli, R.A.
Highlights: R-peak time (RPT) represents the early phase of ventricular depolarization. RPT (ms) in healthy dogs were assessed using the new precordial lead system. In all precordial leads, RPT was significantly different between morphotypes. RPT in V1 was significantly shorter than RPT in V2 to V6 in all morphotypes. Abstract: R-peak time (RPT) is an electrocardiographic parameter that represents the time taken for electrical activation to spread from the endocardium to the epicardium. In human medicine, right ventricular RPT is measured from lead V1 to lead V2, and left ventricular RPT from lead V5 to lead V6 . The aim of the present study was to define RPT duration in a group of clinically healthy dogs with different thoracic conformations. Sixty clinically healthy dogs underwent a 12-lead electrocardiogram recorded using a previously described precordial system. The dogs were allocated into three morphologic groups. In the brachymorphic group, the median and 25th–75th percentiles for RPT in V1 were 10.5 ms (10−12 ms); V2, 18 ms (16.5−20 ms); V3, 19 ms (18−22 ms); V4, 20 ms (17−23.5 ms); V5, 21 ms (18.5−24 ms); and V6 : 22 ms (18.5−25.5 ms). In the mesomorphic group, RPT in V1 was 16 ms (14−18 ms); V2, 22 ms (20−24 ms); V3, 23 ms (21−25 ms); V4, 23 ms (22−25 ms); V5, 25 ms (23−27 ms); and V6, 28 ms (25−30 ms). In the dolichomorphic group, RPT in V1 was 15 ms (13−17 ms); V2, 29 ms (26−32.5 ms); V3, 30 ms (27−33.5 ms); V4, 29.5 ms (26−35 ms); V5, 30 ms (28−34 ms); and V6, 31.5 ms (28−35 ms). RPT in V1 was significantly shorter than RPT in V2 to V6 in all morphotypes ( P < 0.05). In all precordial leads, RPT was significantly different between morphotypes ( P < 0.05). These results are in agreement with previous findings in humans and with the observation that V1 reads the right ventricle and V2 to V6 read the left ventricle. These preliminary data provide RPT ranges in clinically healthy dogs of different morphotypes.